2023
DOI: 10.1063/5.0147231
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on adaptive dynamical systems

Abstract: Adaptivity is a dynamical feature that is omnipresent in nature, socio-economics, and technology. For example, adaptive couplings appear in various real-world systems, such as the power grid, social, and neural networks, and they form the backbone of closed-loop control strategies and machine learning algorithms. In this article, we provide an interdisciplinary perspective on adaptive systems. We reflect on the notion and terminology of adaptivity in different disciplines and discuss which role adaptivity play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 532 publications
0
2
0
Order By: Relevance
“…In this study, we propose adaptive time delay to effectively manage this persistence-responsivity tradeoff in collective motion. Adaptivity, which involves the ability to adapt to changes in external conditions, has been observed in diverse domains such as biology, physics, and social science (37). For the collective motion in nature, it has been found that fish groups can fine-tune their critical point in response to environmental risk and noise levels (38,39).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose adaptive time delay to effectively manage this persistence-responsivity tradeoff in collective motion. Adaptivity, which involves the ability to adapt to changes in external conditions, has been observed in diverse domains such as biology, physics, and social science (37). For the collective motion in nature, it has been found that fish groups can fine-tune their critical point in response to environmental risk and noise levels (38,39).…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve maximum resource utilization, it is necessary to design reasonable dynamics for the links' prices (i.e., the edges' states) [20,21]. In biological neural networks, the facilitation of synapses can be seen as dynamic behavior of edges, where the adaptability of synaptic dynamics leads to the emergence of chaotic dynamic behaviors [22,23]. In transportation networks, reasonable paths (edges) are crucial for the stable operation of the transportation network [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging complex network analysis and dynamical modeling, researchers can investigate how alterations in brain network organization are related to neurological disorders (see e.g., Stam, 2014 ). Moreover, understanding the mechanisms by which synaptic adaptation influences network dynamics can provide insights into disease pathology and potential therapeutic targets (see e.g., Berner et al, 2023 ; Sawicki et al, 2023 ). Translational studies involving both human subjects and animal models, such as mice, facilitate the validation of findings across species and provide valuable insights into the generalizability of therapeutic interventions.…”
mentioning
confidence: 99%